The Nurse-Tuberculosis Patient Relationship according to Imogene King's Theory of Goal Achievement - Grangeiro Bringel Silva, Ingrid (2025)
Introduction: One of the main aspects in the fight against tuberculosis are the actions developed in Primary Health Care (PHC). At this level of care, the nurse's continuous contact through the nursing consultation allows them to maintain a relationship with the sick population. Regarding the nurse-patient relationship for establishing a bond and the compliance with   tuberculosis treatment, we understand the importance of Imogene King's theoretical framework for structuring the nurse-patient interaction and offering a dynamic for this process. Objective: To analyze the nurse-tuberculosis patient relationship  based on Imogene King's Theory of Goal Achievement. Method: A descriptive study with a qualitative approach, with 14 PHC nurses, selected by convenience. Data were collected from August to November 2018 through semi-structured interviews based on Imogene King's Meta-Oriented Nursing Record. The data were analyzed qualitatively using the IRAMUTEQ software. The research was approved by the Ethics Committee. Results: After the analysis, four classes emerged: 1) relationship established on the basis of welcoming; 2) nurse-tuberculosis patient  relationship and the support of other professionals and family members; 3) relationship established towards treatment compliance; and 4) relationship established to confront prejudice associated with tuberculosis. Conclusion: The welcoming, the family, and the bond between the professional, the patient and Primary Health Care team strengthen the coping with the disease and reinforce the compliance with the pharmacological treatment.